2018
DOI: 10.3389/fimmu.2018.00411
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies May Predict Immune-Related Toxicity: Results from a Phase I Study of Intralesional Bacillus Calmette–Guérin followed by Ipilimumab in Patients with Advanced Metastatic Melanoma

Abstract: Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of advanced melanoma. The first ICI to demonstrate clinical benefit, ipilimumab, targets cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4); however, the long-term overall survival is just 22%. More than 40 years ago intralesional (IL) bacillus Calmette–Guérin (BCG), a living attenuated strain of Mycobacterium bovis, was found to induce tumor regression by stimulating cell-mediated immunity following a localized and self-limiting infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Tremendous efforts have been made to identify potential predictive biomarkers for IC-therapy-induced irAEs. These efforts include evaluation of immune cell phenotyping (16), cytokine assays (17), immune repertoire analysis (18), genetic variability of immune regulation (19), gastrointestinal microbiome diversity (20), and autoantibodies (21), etc. Among these potential biomarkers, autoantibodies have garnered particular interest as they can be easily detected from minimally invasive blood collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tremendous efforts have been made to identify potential predictive biomarkers for IC-therapy-induced irAEs. These efforts include evaluation of immune cell phenotyping (16), cytokine assays (17), immune repertoire analysis (18), genetic variability of immune regulation (19), gastrointestinal microbiome diversity (20), and autoantibodies (21), etc. Among these potential biomarkers, autoantibodies have garnered particular interest as they can be easily detected from minimally invasive blood collection.…”
Section: Discussionmentioning
confidence: 99%
“…Among these potential biomarkers, autoantibodies have garnered particular interest as they can be easily detected from minimally invasive blood collection. A recent study investigating the autoantibody repertoire of a small number of patients with advanced metastatic melanoma treated with ipilimumab demonstrated that patients who developed irAEs were characterized by increases in the repertoire of autoantibodies directed against both self and cancer antigens at time points that preceded the development of the toxicity (21). Another recent study identified increased levels of specific B cell populations, including antibody-producing plasmablasts, in patients receiving combination IC therapy treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, BCG has been used since the 1970s to stimulate regression in melanoma and in more recent years and is widely applied as standard therapy for early stage bladder cancer (Alexandroff et al 1999 ). In an attempt to exploit this approach, we recently undertook an early phase clinical trial with intraregional BCG combined with the CTLA4 inhibitor Ipilimumab (Da Gama Duarte et al 2018 ). This trial was discontinued prematurely because of severe auto-immune toxicity in some patients, demonstrating that the approach has the potential to be highly immuno-stimulatory but that some selectivity for cancer may be important in order to constrain toxicity.…”
Section: Defined Antigensmentioning
confidence: 99%
“…High mutation burden is associated with survival benefits from ICB therapy, but autoantibodies may also predict the efficacy of immune checkpoint inhibitors (ICIs) (De Moel et al, 2019). However, recent studies have demonstrated that autoantibodies correlate with immune checkpoint therapy-induced toxicities (Da Gama et al, 2018;De Moel et al, 2019;Tahir et al, 2019). Since the mechanism of ICB therapy is to mediate non-specific suppression of T cells by negative costimulatory signals, it may break the balance of autoimmunity and lead to the activation of autoreactive B cells that produce autoantibodies (Pardoll, 2012;Oh et al, 2017).…”
Section: Neoantigen Load Associates With Immune Checkpoint Inhibitorsmentioning
confidence: 99%